MENGEMBANGKAN KREATIVITAS ANAK DENGAN ALAT PERMAINAN EDUKATIF BLOCKS PIPE - warsono warsono; Ervin Nurul Affrida (incrementapedia, 2019)
This research will be based on quantitative research by the fact still learning of classical and a lack of educational gaming device to develop children's creativity. The purpose of the research to answer the problems: "is there any influence the use of blocks pipe educative games tool to development of children's creativity Group B in TK Dharma Wanita Blukon Lumajang?".This research was conducted with a sample in TK Dharma Wanita wich the whole subject totaled 35 children from 5-6 year, consisting of 16 boys and 19 girls. The collected by observation performance sheets during observation with partisipation.. Data analyzed by the statistical analysis (pre-experiment) with the one-group pretest-posttest design. The results of the analysis of the data showed that the value of ttest = 16.67 is greater than the significance level ttable 2.035 0.05 and 0.01 significance level at 2.441 which means our nihil hypothesis (H0) is rejected and the working hypothesis (HI) are accepted. Based on these results it can be concluded that with blocks pipe educative games tool children become excited and happy to learning in the classroom, and can enhance children's creativity Group B in TK Dharma Wanita Blukon Lumajang.